The Passive Contact Stability of Blue Sheep Hoof Based on Structure, Mechanical Properties, and Surface Morphology - Kui, Hailin; Liu, Xiangyu; Liu, Jing; Liang, Wei; Zhang, Shiwu; Qian, Zhihui; Ren, Lei (Frontiers in Bioengineering and Biotechnology, 2020)
As the only component that contacts the ground and rock, the hooves of blue sheep may play a crucial role in their excellent climbing abilities. In this study, we used a combination of techniques, including scanning electron microscopy, infrared spectroscopy and nanoindentation, to characterize the surface morphology, structure, material composition and mechanical properties of blue sheep hoof and investigate the potential contributions of these properties to the establishment of passive contact stability. Straight and curled microscopic lamellar morphology were found on the hoof surfaces. The cross section of the hoof revealed four layers, and each layer had a unique structure. Finite element analysis was employed to verify that the surface morphology and microstructure effectively contributed to the slip resistance and impact cushioning, respectively. Analyses of the energy and infrared spectra showed that the organic and inorganic substances in different regions of the hoof had similar components but different contents of those components. The hoof was mainly composed of keratin. From the outside to the inside, gradients in both the modulus and hardness were observed. These factors help the hoof alleviate high impact strengths and increase contact stability. These findings further our understanding of the unique mechanism of blue sheep hoof and may help in the development of novel biomimetic materials and mechanical components with enhanced friction and contact stability properties.